TEACHERS’ PERCEPTION ON REFLECTIVE TEACHING - Ginan Muhammad; Nenden Sri Lengkanawati (E-Amal: Jurnal Pengabdian Kepada Masyarakat, 2024)
The purpose of this study is to know and investigate the teachers’ perception on reflective teaching. This research used qualitative method, with selected the questionnaire as the research instrument of the data collection. The findings of this research showed that the reflective teaching is applied, the teachers tend to observe and evaluate their teaching performance. The responses from eight English teachers at junior high school, as the excellent teachers, indicates that they are used the reflective teaching in their teaching performance which including practical, cognitive, learner, and meta-cognitive. According to English teachers’ opinion that reflective teaching could be the way to improve a teaching skill, to observe what was going on, and to evaluate whether it is successful or not. The conclusion of this research is the teachers were concerned with satisfaction and improvement and teaching performance.